Double Burden of Professional and Domestic Roles: Work-Family Conflict, Workload, and Job Stress as Predictors of Performance among Female Healthcare Workers in Hospitals - Rina Masruroh; Deri Prayudi; Aris Budiman; Winda Oktaviani; Dini Alviani (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Female healthcare workers in Indonesia face dual demands from professional and domestic roles, which may affect their work performance. Objective: This study examines the simultaneous and partial effects of work-family conflict (WFC), workload, and work stress on the performance of female healthcare workers, drawing on Role Conflict Theory, Conservation of Resources Theory, and Job Demands-Resources Theory. Methods: A quantitative cross-sectional survey was conducted among 130 female healthcare workers in hospitals in Kuningan Regency, West Java, selected through purposive sampling. Data were collected using a seven-point Likert-scale questionnaire and analyzed using multiple linear regression. Results: WFC and work stress had positive and significant effects on performance, with coefficients of 0.374 (p=0.014) and 0.146 (p=0.022), respectively. In contrast, workload had a negative and significant effect (B=−0.397; p=0.001) and was the strongest predictor based on its standardized coefficient (β=−0.298). Simultaneously, WFC, workload, and work stress significantly affected performance (F=22.687; p<0.001), explaining 35.1% of its variance (R²=0.351). Conclusion: The findings indicate that work pressure does not uniformly impair performance in the collectivist Indonesian context. WFC and work stress may function as performance-enhancing factors when supported by adaptive and professional conditions, whereas workload remains a critical constraint requiring organizational intervention. These findings highlight the importance of culturally sensitive human resource policies that prioritize workload management while providing appropriate support for female healthcare workers.